From Silent Retention to Pelvic Sepsis: Vaginoscopic Removal of a Vaginal Foreign Body followed by Laparoscopic Drainage of Tubo Ovarian Abscess in a 13 Year Old (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Vaginal foreign bodies are uncommon in adolescents and often present with nonspecific or absent genital symptoms, leading to delayed diagnosis. Common manifestations include vaginal discharge, bleeding, recurrent infection, or pelvic pain, although some patients may remain asymptomatic. Prolonged retention may result in chronic inflammation, adhesions, pelvic inflammatory disease, and tubo-ovarian abscess formation. Early imaging and vaginoscopic evaluation are essential for timely diagnosis and prevention of complications.Aim & Objective: To highlight an unusual presentation of a vaginal foreign body in an adolescent girl without genital symptoms and to emphasize the importance of imaging and multidisciplinary management in preventing complications.Case Presentation: A 13-year-old premenarchal girl presented with intermittent lower abdominal pain, fever, and vomiting for two weeks without vaginal complaints. Ultrasonography suggested bilateral adnexal masses with right hydrosalpinx and a possible vaginal foreign body. Contrast-enhanced MRI revealed bilateral tubo-ovarian abscesses with a suspected vaginal foreign body. Psychiatric and forensic evaluations were performed due to medicolegal concerns. Diagnostic vaginoscopy under general anaesthesia identified a cylindrical plastic lipstick cap measuring 3 × 2 cm lodged transversely in the upper vagina with adhesions and pus collection.Result: The foreign body was successfully removed under vaginoscopic guidance with minimal trauma, followed by laparoscopic drainage of bilateral tubo-ovarian abscesses. The patient recovered without complications following multidisciplinary management.Conclusion: Vaginal foreign bodies should be considered in adolescents presenting with unexplained abdominal or pelvic symptoms, even in the absence of genital complaints. Early imaging, prompt diagnosis, and multidisciplinary evaluation are essential to avoid delayed treatment and serious complications.